2010
DOI: 10.1109/jqe.2010.2052352
|View full text |Cite
|
Sign up to set email alerts
|

Virtually Isotropic Transmission Media With Fiber Raman Amplifier

Abstract: -We report a theoretical study and simulations of a novel fiber-spin tailoring technique to suppress the polarization impairments, namely polarization mode dispersion (PMD) and polarization dependent gain (PDG), in fiber Raman amplifiers. Whereas use of depolarizer or multiplexing pump laser diodes with a final degree of pump polarization of 1% for periodically spun fiber results in PDG of about 0.3 dB, we demonstrate that application of just a two-section fiber (where the first part is short and has no spin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 15 publications
2
31
0
Order By: Relevance
“…Varying signal SOPs at the input of fiber Raman amplifier leads to uncontrollable output gain variation. Maximum of the gain variation is defined as polarization dependent gain (PDG) [4][5][6][7][8]. Traditional PMD suppression technique is based on spinning the fiber periodically and results in PMD suppression below 0.04 ps/km 1/2 [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Varying signal SOPs at the input of fiber Raman amplifier leads to uncontrollable output gain variation. Maximum of the gain variation is defined as polarization dependent gain (PDG) [4][5][6][7][8]. Traditional PMD suppression technique is based on spinning the fiber periodically and results in PMD suppression below 0.04 ps/km 1/2 [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional PMD suppression technique is based on spinning the fiber periodically and results in PMD suppression below 0.04 ps/km 1/2 [2,3]. However, this PMD suppression is accompanied with a simultaneous increase in the Raman PDG [5][6][7][8]. The new approach developed by Sergeyev et al [7,8] have shown that it is possible to simultaneously mitigate both PDG and PMD by using a fiber with a particular spin profile or, more specifically, a two-section fiber ('two-section approach') in which the first section has no spin and the second one is periodically spun.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations